2019
DOI: 10.13075/mp.5893.00757
|View full text |Cite
|
Sign up to set email alerts
|

General and specific individual post-traumatic stress disorder-related mechanisms among paramedics

Abstract: StreszczenieWstęp: Ratowników medycznych charakteryzuje podwyższone ryzyko wystąpienia zaburzeń po stresie traumatycznym. Celem zrealizowanego projektu badawczego było wskazanie specyficznych korelatów zespołu stresu pourazowego pojmowanych w kategoriach zasobów i deficytów emocjonalno-poznawczych pod postaciami aleksytymii, ruminacji i strategii radzenia sobie ze stresem w tej grupie zawodowej. Materiał i metody: W 3 niezależnych badaniach, przeprowadzonych w pierwszej połowie 2017 r. w województwie wielkopol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 8 publications
3
10
0
Order By: Relevance
“…As we expected, the analysis results showed that in the studied group, alexithymia was not highly correlated with symptoms of PTSD. A similar effect was observed in comparable studies conducted on emergency workers [ 41 , 56 ]. In this context, it is difficult to clarify whether alexithymia is a risk factor for PTSD or its consequences.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…As we expected, the analysis results showed that in the studied group, alexithymia was not highly correlated with symptoms of PTSD. A similar effect was observed in comparable studies conducted on emergency workers [ 41 , 56 ]. In this context, it is difficult to clarify whether alexithymia is a risk factor for PTSD or its consequences.…”
Section: Discussionsupporting
confidence: 88%
“…Different PSAPs may present different job demands as well as resources. These issues may limit the representativeness of the obtained results [ 56 ]. Further, the lack of a control group (nonemergency workers) or comparative group (other emergency workers) is a major limitation in our study [ 57 , 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…The aim of the current study was to establish the role of personal resources (resilience) in the experience of stress by paramedics during the COVID-19 pandemic. Resilience was taken as a measure of personal resources, as during a pandemic situation, strategies of coping with stress are revealed to be insufficient, especially against traumatic stress (Jasielska and Ziarko, 2019).…”
Section: The Aim Of the Studymentioning
confidence: 99%
“…She indicated that personal resources such as coping strategies were not sufficient coping mechanisms for dealing with traumatic stress. (Jasielska & Ziarko, 2019). In Khan research anxiety was reported by 60% of respondents, 32% of respondents reported depression, around 50% of the respondents were exposed to shift work sleep, 33% reported insomnia, 78% reported severe fatigue, and 23% reported excessive daytime sleepiness (Khan disorders et al, 2018).…”
Section: Consequences Of Stress Among Paramedic Groupmentioning
confidence: 99%
“…Jasielska study showed that more than 50%of paramedics showed symptoms of post-traumatic stress disorder, which can be a prognostic factor for the development of PTSD among that group (Jasielska & Ziarko, 2019). She indicated that personal resources such as coping strategies were not sufficient coping mechanisms for dealing with traumatic stress.…”
Section: Consequences Of Stress Among Paramedic Groupmentioning
confidence: 99%